2014
DOI: 10.1111/gcb.12446
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of no instrument is guaranteed: a reply to Rosenstock et al.

Abstract: Global Change Biology5463-5469. Zhao Y, Pan Y, Rutherford J, Mitloehner FM (2012) Estimation of the interference in multi-gas measurements using infrared photoacoustic analyzers. Atmosphere, 3, 246-265.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Flux measurements of N 2 O and CO 2 were taken daily during the first 5 days after every residue application, every second day in week 2 and 3, every third day in week 4–6, and once a week until the next residue application or the end of the experiment (153 flux measurements in 750 days). The flux measurement protocol largely followed that of previous studies 34 47 and was in agreement with good measurement practices as formulated by Rosenstock et al 42 and Igbal et al 48 49 . Polypropylene flux chambers equipped with two rubber septa were placed on the mesocosm for approximately 30 minutes.…”
Section: Methodssupporting
confidence: 57%
“…Flux measurements of N 2 O and CO 2 were taken daily during the first 5 days after every residue application, every second day in week 2 and 3, every third day in week 4–6, and once a week until the next residue application or the end of the experiment (153 flux measurements in 750 days). The flux measurement protocol largely followed that of previous studies 34 47 and was in agreement with good measurement practices as formulated by Rosenstock et al 42 and Igbal et al 48 49 . Polypropylene flux chambers equipped with two rubber septa were placed on the mesocosm for approximately 30 minutes.…”
Section: Methodssupporting
confidence: 57%
“…Weekly and subweekly measurements were performed following N fertilizer application and rainfall events when emissions were expected to be large. At an Iowa site nearby to ours and of the same soil type, daily measurements of N 2 O emissions demonstrated few emissions when the soil temperature was <10°C (Jarecki, Parkin, Chan, Hatfield, & Jones, ) and daily N 2 O measurements at another nearby research site demonstrated that ~40% of the total annual emissions occurs during times of high flux rates that would scale to >46 kg N 2 O‐N ha −1 year −1 (Iqbal et al., ; USDA‐ARS GRACEnet database).…”
Section: Methodsmentioning
confidence: 92%
“…A tree's age, genotype, functional traits, and mechanisms of acclimation (64,66,67) are all important determinants of growth responses to drought, which can decouple the relationship between RWI and mortality. Importantly, our predictions of vulnerability might understate the risk of mortality at dry-range edges if there are thresholds in the relationship between tree growth and mortality (68). For example, trees likely require a minimum amount of growth to survive (68); therefore, the same percentage growth decline could be more harmful for slow-growing trees located at their dry-range edge than for trees growing in mesic areas (10).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our predictions of vulnerability might understate the risk of mortality at dry-range edges if there are thresholds in the relationship between tree growth and mortality (68). For example, trees likely require a minimum amount of growth to survive (68); therefore, the same percentage growth decline could be more harmful for slow-growing trees located at their dry-range edge than for trees growing in mesic areas (10). Future research that characterizes these nonlinear responses to drought could improve predictions of climate impacts (42,43).…”
Section: Discussionmentioning
confidence: 99%